2008
DOI: 10.1016/j.jcm.2008.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic disk height increase after a trial of multimodal spine rehabilitation and vibration traction: a retrospective case series

Abstract: Objective: Although spinal decompression therapy has been touted as an effective treatment of disk pathologies, there is little existing research that specifically uses disk parameters as an outcome measure after a course of spinal decompression therapy. Our study presents multidimensional outcomes after a structured protocol of multimodal chiropractic rehabilitation and uses a radiographic parameter of disk disease as an indication of the effects of a vibration traction decompression-type table. Clinical Feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…16) Additionally, the reported values under 55% BW loading were 2.8 and 2.3 mm, respectively. 1 15) Figs. 11 and 12 show the comparison of results between these studies and ours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16) Additionally, the reported values under 55% BW loading were 2.8 and 2.3 mm, respectively. 1 15) Figs. 11 and 12 show the comparison of results between these studies and ours.…”
Section: Discussionmentioning
confidence: 99%
“…11 13) Studies showed that traction loading on the lumbar area of the spinal column should be approximately between 45% and 60% of the BW. 1 14 15 16) In this study, firstly we used 45% and 55% of the BW as traction loading. Since the traction belt imposes the load on the L5 vertebra, we placed the load on L5 and fixed L1 in our model.…”
Section: Methodsmentioning
confidence: 99%